ANALYSIS OF THE DIFFERENCE BETWEEN CONVENTIONAL BANK INTEREST AND SHARIA BANK PROFIT SHARING: ANALISIS PERBEDAAN ANTARA BUNGA BANK KONVESIONAL DAN BAGI HASIL BANK SYARIAH - Audina, Mia (LPPM UPMI, 2023)
With the development of the banking world in the community regarding the existence of interest called usury', regulations emerged that permitted banking business activities based on sharia principles that do not use interest but use profit sharing. The difference between interest at conventional banks and profit sharing at Islamic banks is that interest is the actualization of usury which is definitely forbidden by Islam. The equation that is hard to argue with is that actually the application of interest to banks has more harm than good, profit sharing is something that is covered by sharing the results of business between the provider of funds and the fund manager. The distribution of business results occurs between the bank and the depositor, or the bank and the beneficiary customer. Banks as intermediary institutions collect funds from people who experience a surplus of funds and distribute them back to people who need funds. The most important allocation of funds for banking activities is the allocation of loan funds, which are known as conventional-based credit and sharia-based financing. The difference between credit and financing lies in the advantages that wanted.